Digital economy Opportunities and risks for small and medium enterprises - Abdurakhmanov Abdulaziz (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The variety of shifts described in the preceding sub-sections present both opportunities and dangers for MSMEs particularly in developing and least developed economies. One set of opportunities arises from the unique new business models of digital economy firms. The other issues from the spread of digitalization, automation, and artificial intelligence in the real-world sectors in which most MSMEs operate. How these play out will depend on how digitally ready MSMEs are and how supportive government policy is.